CEO turnover in a competitive assignment framework - Eisfeldt, Andrea L.; Kuhnen, Camelia M. (Journal of Financial Economics, 2013)
There is widespread concern about whether Chief Executive Officers (CEOs) are appropriately punished for poor performance. While CEOs are more likely to be forced out if their performance is poor relative to the industry average, overall industry performance also matters. This seems puzzling if termination is disciplinary, however, we show that both absolute and relative performance-driven turnover can be natural and efficient outcomes in a competitive assignment model in which CEOs and firms form matches based on multiple characteristics. The model also has new predictions about replacement managers' equilibrium pay and performance. We document CEO turnover events during 1992–2006 and provide empirical support for our model.